1992
DOI: 10.1007/bf02352065
|View full text |Cite
|
Sign up to set email alerts
|

The results of surgery for intracerebral hematomas

Abstract: Our retrospective study included 104 patients (28 female and 76 male) with intracerebral bleeding, treated between 1978 and 1988 in the Neurosurgical Clinic of the Medical University in Hannover. The average age was 43 years. 53 patients presented with traumatic intracerebral bleedings, and 51 with spontaneous hematomas. 31 patients with spontaneous hematomas were operated: among these a good or satisfactory result was obtained in 19 patients, and 12 died. Of the 20 non-operated patients, a good or satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Although there are clinical trials for spontaneous cerebral hemorrhage removal, there are still no clinical trials specifically for TICH hematoma removal ( Table 1). As early as the 1990s, Zumkeller et al (1992) found that the incidence of undesirable prognosis in the hematoma removal group of TICH patients was better than that in the non-surgical group of TICH patients. Similarly, in a single-center retrospective study, Choksey et al (2009) found that in patients with a low GCS score whose TICH hematoma volume was greater than 16 ml, the proportion of patients with undesirable prognosis in the hematoma removal group was 38% less than that in the non-surgical group (56%).…”
Section: Intervention Strategies and Clinical Trialsmentioning
confidence: 99%
“…Although there are clinical trials for spontaneous cerebral hemorrhage removal, there are still no clinical trials specifically for TICH hematoma removal ( Table 1). As early as the 1990s, Zumkeller et al (1992) found that the incidence of undesirable prognosis in the hematoma removal group of TICH patients was better than that in the non-surgical group of TICH patients. Similarly, in a single-center retrospective study, Choksey et al (2009) found that in patients with a low GCS score whose TICH hematoma volume was greater than 16 ml, the proportion of patients with undesirable prognosis in the hematoma removal group was 38% less than that in the non-surgical group (56%).…”
Section: Intervention Strategies and Clinical Trialsmentioning
confidence: 99%
“…57 Indications for surgery include hematoma volume greater than 3 cm in diameter, brainstem compression, or hydrocephalus. 58 External ventricular drain placement alone is not sufficient for decompression and may lead to shifts in the pressure gradient across the tentorium that may increase the risk of upward herniation. 59 There are no randomized controlled trials and likely none forthcoming in the future due to a lack of clinical equipoise in favor of surgery; however, case series data suggest improved outcomes and mortality with surgery compared with medical management in cerebellar ICH.…”
Section: Surgical Management Posterior Fossa Intracerebral Hemorrhagementioning
confidence: 99%
“…Several authors [4-6] have compared surgery with conservative treatment in single center retrospective series and recommended surgery for larger TICHs even if patients were in an apparently good clinical state initially. Matheisen et al [4] found that patients with an admission Glasgow Coma Score of at least 6 and a lesion volume of at least 20 mL who had surgery without previous neurological deterioration had significantly better outcomes than those who did not have surgery or had surgery after deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Choksey et al [5] found that 38% of patients with a low GCS and a volume of the TICH >16 mL who had surgery had a poor outcome compared to 56% of those who did not have surgery. Zumkeller et al [6] found that the poor outcome rate in the operated patients was 29% compared to 59% in the non-operated group. Such associations do not represent true causes and effects or treatment benefits or harm.…”
Section: Introductionmentioning
confidence: 99%